Neurological Manifestations among Patients with HIV #x2013; Active Tuberculosis co Infection (Global Journal of Medical Research, 2020)
At least one-third of the 35.3 million people living with HIV worldwide are infected with latent tuberculosis. Tuberculosis is the most common presenting illness among people living with HIV, including those who are taking antiretroviral treatment. There were an estimated 1.1 million HIV positive new TB cases globally in 2012. Around 75% of these people live in sub- Saharan Africa. Despite its great burden, neurological manifestations have not been described yet in patients with HIV-active tuberculosis, although tuberculosis and HIV have synergistic influence on immunity system which may contribute to change in prevalence or severity of CNS involvement in patients with HIV-active TB co infection. Objectives: To study neu rological manifestations in patients with HIV-active tuberculosis.